THE ROLE OF INFLAMMATORY MARKERS AS IL-6, TNF-a, INF-y WITH PSORIATIC ARTHRITIS AND RATES OF COMORBIDITY - Khilola T. Mirakhmedova; Gulizebo B. Saidrasulova; Nilyufar R. Mukhsimova (Central Asian Journal of Medicine, 2023)
Psoriatic arthritis (PsA) is simultaneously affected by the peripheral joints and skin in rheumatology. Several proinflammatory cytokines are produced in PsA and they induce inflammation of joints, nails, skin, and also internal organs. Serum cytokines levels play an important role in the pathogenesis of PsA by stimulating autoimmune reactions and influencing them continuously. Purpose. This study aimed to identify how to influence the serum level of inflammatory markers as IL-6, TNF-a, and INF-y to disease course and duration. As well as, determine triggers and comorbid conditions of the disease. Material and Methods. The study included a number of 170 participants. The participants were divided into 2 groups as 150 patients with PsA who fulfilled the CASPAR criteria and 20 healthy controls. Patients underwent history, clinical examination, x-ray, assessment of Psoriasis Area and Severity Index (PASI) score, and were determined HLA-27 gene, the serum level of inflammatory markers as IL-6, IFN-y, and TNF-a. Blood samples were collected from all participants. The serum levels of inflammatory markers were measured by solid-phase sandwich enzyme-linked immunosorbent assay technique. Result. In the early and late stages of the disease, the serum level of inflammatory markers as IL-6, TNF-a, and INF-y in patients with PsA was significantly higher (130,2pg/ml, 292,1 pg/ml, and 80,2 pg/ml in early-stage and 140,0 pg/ml, 362,2 pg/ml, and 82,4 pg/ml respectively p<0,05) than the healthy group. Significantly elevated serum TNF-a was higher than INF-y and IL-6 in the early and late stages of PsA patients. In patients with PASI<30 all cytokines levels were reliably lower than in patients with PASI>30. Erosion arthritis was found in x-ray, who were increased levels of cytokines than non-erosion arthritis were common almost in lower levels of cytokines. Moreover, cytokines HLA-B27 gene who was positive, are a considerably rise than negative patients. Conclusion. In our study triggers of disease were found as psoriasis, trauma, stress, and hypothermia. Elevated serum levels of cytokines had occurred in the early and late stages of the disease. Notably, the early phase of disease was initially increased TNF-a levels. Elevated serum levels of cytokines were correlated with activity, the severity of PsA and PASI scores.